Xenotropic murine leukemia virus-related virus (XMRV) in prostate cancer cells likely represents a laboratory artifact - Yang, Jiawen; Battacharya, Partho; Singhal, Ruchi; Kandel, Eugene S (Oncotarget, 2011)
The prevalence of xenotropic murine leukemia virus-related virus (XMRV) in human population and its involvement in prostate cancer are subjects of ongoing research and debate. 22Rv1, which is a human cell line that serves as a common model of androgen-independent prostate cancer, was recently reported to carry infectious copies of XMRV. 22Rv1 was derived from a prostate cancer xenograft CWR22 that was serially passaged in immunodeficient mice. Based on the analysis of the DNA from CWR22 and 22Rv1, we present evidence against the presence of XMRV in CWR22 and, by inference, the tumor, from which CWR22 and 22Rv1 were established. While the presence of XMRV in 22Rv1 is likely to be an artifact, it may be a significant factor in determining the biological properties of this cell line. This consideration warrants additional caution for the interpretation of the relevance of the studies, which utilize this popular cell line as a model. It also invites a closer look at the sources of viral contamination in xenografts and cultured cells, as well as in the experiments that allege the presence of this virus in human cells and populations.